2021
DOI: 10.1101/2021.02.17.431672
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TuMV infection alters miR168/AGO1 and miR403/AGO2 systems regulation in Arabidopsis

Abstract: Viral infections trigger a strong response of the plant RNA silencing machinery. The cargo protein AGO1 has a well-established role in siRNA loading. Several plant viruses have convergently evolved a molecular counter-attack reliant on inactivation of the AGO1-based plant defense by altering the regulatory loop that comprises miR168 and AGO1. Upon viral infections, another AGO protein, AGO2, is induced. AGO2 is in turn post-transcriptionally regulated by miR403. The simultaneous study of both regulatory system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Another study revealed that upon TuMV infection, the mature form of miR403 was induced (and consistently the pri-miR403 level was reduced). Moreover, AGO2 mRNA was strongly induced suggesting that upregulation could escape AGO2 mRNA from AGO1-miR403 repression [28]. Indeed, gibberellic acid, UV irradiation and bacterial infection upregulated AGO2 mRNA revealing that AGO2 was regulated by a variety of biotic and abiotic stresses [20,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Another study revealed that upon TuMV infection, the mature form of miR403 was induced (and consistently the pri-miR403 level was reduced). Moreover, AGO2 mRNA was strongly induced suggesting that upregulation could escape AGO2 mRNA from AGO1-miR403 repression [28]. Indeed, gibberellic acid, UV irradiation and bacterial infection upregulated AGO2 mRNA revealing that AGO2 was regulated by a variety of biotic and abiotic stresses [20,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that some miRNAs have a significantly different accumulation in both cultivars, these include miR397‐3p, miR530, miR7122, miR170, and miR403. These miRNAs, which were more abundant in Desiree compared with Eva, have been found to be involved in plant responses to stress (Dong & Pei, 2014 ; Kohli et al, 2014 ; Li et al, 2021 ; Manacorda et al, 2021 ; Xia et al, 2013 ). Future research efforts would determine whether these miRNAs are responsible for some of the stress responsive differences between Desiree and Eva.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that some miRNAs have a significantly different accumulation in both cultivars, these include miR397-3p, miR530, miR7122, miR170, and miR403. These miRNAs, which were more abundant in Desiree compared with Eva, been found to be involved in plant responses to stress (Dong & Pei, 2014;Kohli et al, 2014;Manacorda et al, 2021;Xia et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…AGO1 has been revealed to be involved in antiviral response to turnip crinkle virus ( Azevedo et al, 2010 ) and CMV ( Zhang et al, 2006 ). AGO2 plays an essential role in resisting CMV ( Harvey et al, 2011 ), PVX ( Jaubert et al, 2011 ), and TuMV ( Manacorda et al, 2021 ). AGO1 and AGO7 function cooperatively to ensure the removal of viral RNAs with different secondary structures ( Qu et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%